Genetic potential and heritability estimates of yield traits in F3 segregating populations of bread wheat - Jan, Soshma; Mohammad, Fida; Khan, Fahim Ullah (International Journal of Environment, 2015)
An experiment comprising of 24 wheat genotypes was undertaken during 2011-12, at New Developmental Research Farm, The University of Agriculture Peshawar, to elucidate information on the nature and magnitude of genetic variability, index of transmissibility and assessing the level of genetic improvement of the quantitative characters. The experimental material comprising 19 F3 populations along with their 5 parents of bread wheat were evaluated in randomized complete block design (RCBD) with three replications. Analysis of variance exhibited highly significant (P ≤ 0.01) differences among genotypes for all the traits studied. F3 population Ghaznavi-98 x Pirsabak-05 showed maximum mean value for 1000-grain weight (47.3 g) and biological yield (11474.9 kg ha-1), whereas, maximum values for grain yield (4027.3 kg ha-1), and harvest index (48.1%) were observed for Pirsabak-05 x AUP-4006. Moreover, maximum spike length (11 cm) was recorded for cross combination Pirsabak-05 x Pirsabak-04 and Janbaz x Pirsabak-05, respectively. In addition, Pirsabak-04 showed maximum value for number of grains spike-1 (55.0). Genetic variances were of greater magnitude than environmental variances for all the traits except for spike length and 1000-grain weight. Heritability estimates were of higher magnitude ranged from 0.64 to 0.92 for harvest index, biological yield, grain yield, and grains spike-1. Moderate to low heritability (0.40-0.46) was observed for 1000-grain weight, and spike length, respectively. Genetic gain was for spike length (0.48 cm), grains spike-1 (8.57), 1000-grain weight (2.93 g), grain yield (639.87 kg ha-1), biological yield (1790.03 kg ha-1), and harvest index (5.32 %). From high values of heritability and genetic advance, it could be concluded that selection for traits like grains spike-1 suggested good selection criteria and could be effective for future breeding programs. DOI: http://dx.doi.org/10.3126/ije.v4i2.12630 International Journal of Environment Vol.4(2) 2015: 106-115